2020
DOI: 10.3389/fnins.2020.00872
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Neuroimaging Indicators in Monitoring the Effects of Interferon Gamma Treatment in Friedreich’s Ataxia

Abstract: The identification of efficient markers of disease progression and response to possibly effective treatments is a key priority for slowly progressive, rare and neurodegenerative diseases, such as Friedreich’s ataxia. Various imaging modalities have documented specific abnormalities in Friedreich’s ataxia that could be tracked to provide useful indicators of efficacy in clinical trials. Advanced MRI imaging (diffusion tensor imaging, DTI; functional MRI, fMRI; and resting-state fMRI, rs-fMRI) and retinal imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Treatment of the FRDA group was reported only in two studies, mentioned as chronic treatment ( 13 , 30 ) or an ongoing open-label phase II study ( 34 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Treatment of the FRDA group was reported only in two studies, mentioned as chronic treatment ( 13 , 30 ) or an ongoing open-label phase II study ( 34 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study performed imaging in different types of patients with ataxia, including FRDA, SCA3, and SCA6, analyzing the groups separately and comparing with HC groups (12). (13,30) or an ongoing open-label phase II study (34,35).…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the 12 months open-label extension of the same study showed a potential benefit toward expected disease progression in treated patients ( Lynch et al, 2019 ). More recently, an open-label phase II trial measuring the SARA score and using instrumental evaluations including electro/echocardiography ( Vavla et al, 2020b ) and Diffusion Tensor Magnetic Resonance Imaging of the brain ( Vavla et al, 2020a ), was completed over an observation time of 18 months. The progression of SARA was completely halted during IFN-γ treatment and slightly resumed after termination of the treatment.…”
Section: Biological Drugsmentioning
confidence: 99%